PEMBINAAN KARAKTER MELALUI PEMBELAJARAN TARI DI SMPNEGERI20 PADANG - Dewanti, Ririn; Yuliasma, Yuliasma (SENDRATASIK UNP, 2019)
Abstract This study aimed to determine and described the effect of using internet media on students learning outcomes at SMP Negeri 20 Padang.The type of this research was quantitative research using experimental method. The samples in this study consisted of two study groups taken by purposive sampling. The research instrument used was in the form of practice. Data collection techniques were conducted by means of literature study, tests and documentation. The steps for analyzing data were normality, homogeneity, and hypothesis test.The results confirmed that the significant differences between class VIII6 (experimental class) and class VIII4 (control class) in students learning outcomes of dance moves at SMP N 20 Padang were. This proved that using internet media could influence students learning outcomes. Then, the average value obtained from the experimental class was 81.5 higher than the control class which is 78.2. According to the results of the hypothesis test, It was tcount> ttable where 3.38> 2.0049 as evidenced by the significant level α 0.05. It meant that there were significant differences between the results of the development of dance movements of students who used internet media with the control class using conventional media (material in school). By using internet media, it was proven that the dance movements for students at SMP N 20 Padang were significantly developed.  Keywords: the effect,  internet media, students learning outcomes, dance art